Les novel·les dels camps de concentració - Vicent Simbor Roig (Caplletra: Revista Internacional de Filologia, 2014)
This study analyzes the testimonial novels on concentration camps «K. L. Reich», by J. Amat-Piniella, «Crist de 200,000 braços», by A. Bartra and «El desgavell» by F. Planes, and compares them with some of the best known novels on concentration camps by European Authors (Primo Levi, Jorge Semproen, Robert Antelme and Imre Kertész). The main aim is to discover what the principal characteristics of such exceptional novels are. I have looked into the relation between autobiographical literature and novelistic fiction, the elaboration of a rather peculiar conception of time and space that makes up the true chronotope of the concentration camp, narrative options with regard to the narrator, etc. The final conclusion is that the testimonial novel describing life in a concentration camp is a model with very clear characteristics.